Implications and explications of police translation of complainants’ sworn statements: evidence lost in translation? - Ralarala, Monwabisi Knowledge (University of the Free State, 2015)
This interdisciplinary case study demonstrates that ‘retelling and rewriting’ of complainants’ legal narratives constitutes translation. The police officers’ (hereafter referred to as transpreters) exercise of translating such narratives from isiXhosa (ST) into English (TT) is quite essential in the administration of justice in a multilingual and multicultural environment such as South Africa, and specifically in the South African Police Service. The challenge (amongst others) in the current system is that traspreters are neither accredited nor posses the necessary credentials to perform this fundamental role and function. The key objectives of this study were investigated by means of scientific papers – both publishable and published as book chapters as well as journal articles in both international and accredited journals. Drawing on various conceptual and analytical frameworks (Sturge 2007, 2009; Asad 2010; Goffman 1981; Dollerup 1999, 2003, 2006, Schiavi 1996 and Chatman, 1978, 1990), the study teases out both micro and macro elements that emanate from 20 voice-recorded and 20 textual translation episodes of sworn statement – which were used as data. The research contributes significantly to scholarship. Apart from calling for a debate on the identifiable flaws of the current model of record construction within the criminal justice system, the study also paints a clear picture of the perpetuation of inequalities and dominance, and points out that these issues seem to have a direct bearing on the failure to observe social justice, access to justice and linguistic human rights in the South African Police Service. Elaborating on research- based explanations for these existing gaps, the study also offers important recommendations that are directed towards the revisiting of the current model of police record construction.
Thesis (Ph.D. (Linguistics and Language Practice))--University of the Free State, 2015
Keywords: Translation; Complainants’ legal narratives; Sworn statements; Administration of justice; Dominance; Transpreters; Social justice; Access to justice; Translating and interpreting; Police -- South Africa; Evidence